(untitled) (GESTIÓN Y TENDENCIAS, 2019)
With the promise of playing in the major leagues by adopting a global standard for financial accounting information, Chile joined IFRS as of 2009. Every financial statement would thus be more complete, more understandable, and more comparable across companies worldwide. For many, however, the only achievement has been to make accounting frameworks more complex and to turn financial statements into endless treatises intelligible only to experts. Ten years after the start, a balance sheet in which not everything was a gain.